Cultural Anchors of Entrepreneurship: Evaluating the Mediating Role of Community Empowerment among Indigenous Papuan Micro-Enterprises - Westim Ratang; Yohanis Rante (Westscience Press, 2026)
Micro-enterprises are a key driver of grassroots economies, and the empowerment of Indigenous Papuan entrepreneurs has been a focal point for the Department of Industry, Trade, Cooperatives, and MSMEs in the City of Jayapura. Diverging from prior studies that primarily discuss the role of local governments in empowering MSMEs descriptively without empirically examining inter-variable mechanisms, this research positions community empowerment as a mediating variable between local culture and entrepreneurial abilities—a relationship yet unexplored within the context of Indigenous Papuan MSMEs. This study aims to investigate the department's role in empowering MSMEs for Indigenous Papuans and analyze the direct and indirect effects of local culture on the entrepreneurial abilities of Indigenous Papuans in Jayapura City through community empowerment. A mixed-method approach was employed for this research (quantitative and qualitative). Quantitative data from 65 Indigenous Papuan micro-entrepreneurs were analyzed using Structural Equation Modeling (SEM) with SmartPLS, while qualitative data were analyzed following the Miles, Huberman, and Saldana model. The findings indicate that local culture significantly influences community empowerment (coefficient 0.470; t-statistic 4.071; p-value 0.000) and entrepreneurial abilities (coefficient 0.445; t-statistic 3.660; p-value 0.000). Community empowerment significantly impacts entrepreneurial abilities (coefficient 0.321; t-statistic 2.704; p-value 0.007). Indirectly, local culture significantly affects entrepreneurial abilities through community empowerment (coefficient 0.151; t-statistic 2.183; p-value 0.029). Local culture and community empowerment collectively account for 43.5% of the variance in entrepreneurial abilities. These findings underscore that preserved local culture, supported by community empowerment, can enhance the entrepreneurial abilities of Indigenous Papuan MSMEs, while also reinforcing the literature on the mediating role of community empowerment in indigenous entrepreneurship contexts.